The last Olympian - Riordan, Rick. (New York Disney Hyperion Books, 2009)
The long-awaited prophecy surrounding Percy Jackson's sixteenth birthday unfolds as he leads an army of young demigods to stop Kronos in his advance on New York City, while the Olympians struggle to contain the rampaging monster, Typhon.
Keywords: Mythology, Greek -- Fiction; Fate and fatalism -- Fiction; Monsters -- Fiction; Animals, Mythical -- Fiction; Titans (Mythology) -- Fiction